A cross-layer approach to the optimal flow, power and rate control for maximum-throughput delivery of VBR traffic over wireless connections. (1st January 2011) - Baccarelli, Enzo; Cordeschi, Nicola; Patriarca, Tatiana; Polli, Valentina
The delivering of variable bit rate (VBR) encoded media contents to nomadic end-users through the 'last-hop' wireless connection, rises up several challenges related to the fading-impaired and time-varying nature of the wireless medium itself. In detail, a still open question concerns the closed-form design of cross-layer control policies to maximise the average throughput while taking into account constraints comprising layers of the protocol stack from the physical (PHY) up to the application (APP) one. To overcome the computational cost entailed by dynamic programming solutions, the approach we follow aims at the maximisation (on a per-slot basis) of the throughput averaged over the fading statistic and conditioned on the queue-state. To show the performance of the proposed controller, (tight) upper and lower bounds have been derived for the average throughput and numerical tests have been presented to give insight into the connection bandwidth vs. queue-delay tradeoff.